Thermodynamics : - Bhattacharjee, Subrata (Pearson Education, 2016)
Thermodynamics: An Interactive Approach employs a layered approach that introduces the important concepts of mass, energy, and entropy early, and progressively refines them throughout the text. To create a rich learning experience for today’s thermodynamics student, this book melds traditional content with the web-based resources and learning tools of TEST: The Expert System for Thermodynamics (www.pearsonhighered.com/bhattacharjee)–an interactive platform that offers smart thermodynamic tables for property evaluation and analysis tools for mass, energy, entropy, and exergy analysis of open and closed systems.